Phase I/II trial of meclofenamate in progressive MGMT-methylated glioblastoma under temozolomide second-line therapy: the MecMeth/NOA-24 trial - Zeyen, Thomas; Potthoff, Anna-Laura; Nemeth, Robert; Heiland, Dieter H.; Burger, Michael C.; Steinbach, Joachim P.; Hau, Peter; Tabatabai, Ghazaleh; Glas, Martin; Schlegel, Uwe; Grauer, Oliver; Krex, Dietmar; et al. (Trials, 2022)
Glioblastoma is the most frequent and malignant primary brain tumor. Even in the subgroup with O-6-methylguanine-DNA methyltransferase (MGMT) promoter methylation and favorable response to first-line therapy, survival after relapse is short (12 months). Standard therapy for recurrent MGMT-methylated glioblastoma is not standardized and may consist of re-resection, re-irradiation, and chemotherapy with temozolomide (TMZ), lomustine (CCNU), or a combination thereof. Preclinical results show that meclofenamate (MFA), originally developed as a nonsteroidal anti-inflammatory drug (NSAID) and registered in the USA, sensitizes glioblastoma cells to temozolomide-induced toxicity via inhibition of gap junction-mediated intercellular cytosolic traffic and demolishment of tumor microtube (TM)-based network morphology.
Gesehen am 24.01.2023